THE ANALYSIS OF SERVICE QUALITY IMPACT ON CUSTOMERS’ SATISFACTION (Case Study of “Mas Alief” Automotive Workshop Bangkalan.) - Sandra Oktaviana Pinaraswati; Ilya Farida; Sri Susilowati; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the impact of service quality of "Mas Alief" automotive workshop Bangkalan on customer’s satisfaction. The study uses quantitative methods with multiple linear regression analysis techniques, with the dependent variable of service quality consisting of physical evidence, reliability, responsiveness, assurance and care. Whereas, independent variables are in favour of customers’ satisfaction. The research involves 100 respondents with purposive sampling technique. The results showed simultaneous significant impact of service quality variables comprising physical evidence, reliability, responsiveness, assurance and care on customers’ satisfaction. On the contrary, assurance variable partially has no significant impact on customers’ satisfaction of the workshop service. In addition, the variable with dominant impact on consumers’ satisfaction is the care variable. Keywords: Service Quality, Physical Evidence, Reliability, Responsiveness, Assurance, Care, Costumers’ Satisfaction